Overrun Factors during the Construction Phase of Project - Raja Khan Muhammad; Rahman, Ismail Abdul; Nagapan, Sasitharan (International Journal of Sustainable Construction Engineering and Technology, 2021)
The construction sector contributes to a country’s development by providing real solutions to human needs, improving the gross domestic product (GDP), and providing job opportunities. Besides numerous benefits, the construction industry is a resource-driven sector and faces many challenges. One of the challenges is to complete the construction project on time within the budget that is momentous for the client, consultant, and contractor. However, time and cost overrun are the most common anomalies due to improper management of the constructions. Hence, this article aimed to recognize the most affecting causative factors to delays and cost overrun construction projects. The detailed literature and comprehensively reviewed from 49 research articles of the past three decades found that ’delay in the payment’ is the most repeated factor mentioned by 35 researchers in their studies. However, ’poor site management,’ labor, material related factors, and ’delay in design development with errors’ are the most repeated factors reported by the research for the delay and cost overrun. This paper also suggests the appropriate strategies and techniques minimize the causative factors of time and cost overruns uncovered from the previous literature.